Wi-Fi Radiation Negatively Influences Plant Growth and Biochemical Responses of Capsicum annuum L var. Pusa Jwala - Nikalje, Ganesh; Rajam, Pooja (Current Chemical Biology, 2021)
Background: Internet browsing has become an indispensable part of day-to-day life. Computers and the internet have occupied almost all sectors of human life. However, it is an artificial source of electromagnetic radiation, which has adverse effects on all living things in dose-dependant manner. Objective: To understand the impact of electromagnetic radiations on plant, Capsicum annuum L. var. Pusa jwala emitted by Wi-Fi routers. Methods: For the germination experiment, Chilli seeds were kept in close vicinity (5 cm) of a Wi– Fi router for 10 days. For growth and biochemical analysis, different growth and biochemical attributes were studied after 21 days of exposure. Control seeds/plants were kept in another room with almost identical conditions like light, temperature, etc. Plant growth was measured in terms of fresh weight, shoot length, root length, leaf length, leaf breadth and leaf area index. In Biochemical analysis, chlorophyll-a, chlorophyll-b, total chlorophyll, soluble protein, lipid peroxidation and proline contents were measured as per standard protocols. Results: The seed germination in the vicinity of the Wi-Fi router was reduced to 75% and other growth-related parameters like root and shoot length, leaf length, leaf width, leaf area index and fresh weight were significantly reduced. In the biochemical analysis, chlorophyll pigments (Chl. a, b and total chlorophyll) were observed to be reduced by 4.8, 7.2 and 5.7 fold, respectively and protein content reduced by 1.5 fold under the influence of electromagnetic radiations. The product of lipid peroxidation (malondialdehyde) (18 fold) and proline content (10 fold) was found to be increased synergistically. Conclusions: The electromagnetic radiations emitted by the Wi-Fi router have a negative influence on the growth and biochemical responses in Chilli plants.
Keywords: biochemical response